The Andean areas of pathology phlebotomus - Weiss, Pedro (1953)
On the western slopes of the central and northern, and in some valleys, in a band saw between 800 and 300 meters high is located two diseases transmitted by Phlebotomus, Peruvian Wart and Uta. Malaria in the lower valleys up to 1,800 meters on the western slopes and more height in the Andean valleys. Epidemic typhus in the upper parts of the lower mountains to heights not yet certain, without reaching the coastal desert.